AVENUES OF ENTRY TO THE ACCOUNTING PROFESSION. - Stevenson, R. A. (The Accounting Review, 1931)
There is one major problem confronting the accounting profession that will occupy the attention of the administration of the Association of University Instructors in Accounting in the year 1931. Avenues of entry into the practice of accounting are not clearly defined. It is extremely difficult for a young man who shows some aptitude in this field to determine upon the proper method of preparation to secure admission to the profession. Up to the present time the professional societies have not set forth the qualifications of an accountant or the proper training methods. It seems to the author that the time has come for practitioners and teachers of accounting to attack this problem with a view to establishing a relationship that compares with other professions such as law, medicine and engineering. The present situation perhaps is to be expected in a young and growing profession. Accounting has passed the stage of infancy now and it seems that it should be ready to accept implications involved in being recognized as a profession. There are still some who look upon accounting as a trade or business but most practitioners prefer to be known as professional men and to have their occupation recognized by the public as a profession.